Characterization of a humanized mouse model of Charcot-Marie-Tooth type 1A for the discovery of human PMP22-targeting drugs - Taruta, Atsuki; Matsumoto, Shin-ichi; Masuda, Yasushi; Hiyoshi, Tetsuaki; Harada, Akina; Kosugi, Yohei; Nakashima, Masato (Frontiers in Neurology, 2025)
Background and aimsCharcot–Marie-Tooth type 1A (CMT1A) is the most common inherited demyelinating peripheral neuropathy caused by duplication of the peripheral myelin protein 22 (PMP22) gene. Although there is currently no approved treatment for CMT1A, reducing PMP22 expression has emerged as a promising therapeutic approach. The PMP22-C3 mouse model is a widely used CMT1A model that carries human PMP22 (hPMP22) and mouse Pmp22 (mPmp22) genes, complicating the relationship between reduced PMP22 levels and the recovery of phenotypes by drug candidates targeting only human PMP22. To address this, we developed humanized C3 mouse lines lacking the mPmp22 gene. Here, we characterized these models to confirm their utility as novel disease models for CMT1A.MethodsHeterozygous (hetero-humanized) and homozygous (homo-humanized) hPMP22 transgenic mice, with an mPmp22 homozygous knockout background, were investigated using biochemical, electrophysiological, histopathological, and behavioral analyses.ResultsHomo-humanized mice exhibited abnormal mRNA expression of myelin-related genes, slow nerve conduction velocity, reduced compound muscle action potential, demyelinated peripheral nerves, higher levels of plasma neurofilament light chain, muscle weakness and motor/balance disabilities, alterations in electrical impedance myography, and muscle fiber atrophy. In contrast, the hetero-humanized mice did not display any of the previously described impairments.InterpretationHomo-humanized mice reflect various aspects of CMT1A characteristics in an hPMP22 gene dosage-dependent manner. This model will help us better understand the relationship between PMP22 reduction levels and the recovery of CMT1A-related phenotypes, contributing to the translation of preclinical findings into clinically relevant human treatments and dosing strategies.